The Robotic Social Attributes Scale (RoSAS): Development and Validation - Carpinella, Colleen M.; Wyman, Alisa B.; Perez, Michael A.; Stroessner, Steven J. (2017 12th ACM/IEEE International Conference on Human-Robot Interaction (HRI, 2017)
Accurately measuring perceptions of robots has become increasingly important as technological progress permits more frequent and extensive interaction between people and robots. Across four studies, we develop and validate a scale to measure social perception of robots. Drawing from the Godspeed Scale and from the psychological literature on social perception, we develop an 18-item scale (The Robotic Social Attribute Scale; RoSAS) to measure people's judgments of the social attributes of robots. Factor analyses reveal three underlying scale dimensions-warmth, competence, and discomfort. We then validate the RoSAS and show that the discomfort dimension does not reflect a concern with unfamiliarity. Using images of robots that systematically vary in their machineness and gender-typicality, we show that the application of these social attributes to robots varies based on their appearance.